The Adventure Campaign, a National Initiative to Promote Physical Activity and Healthy Lifestyles Among Finnish Families Through Early Childhood Education and Related Services (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The Finnish Government’s “Get Moving” programme aims to ensure physically active lifestyles for all ages and is supported by the national “On the Move” programme family, which is funded by the Ministry of Education and Culture. The “Joy in Motion” programme, launched in 2015, aims to ensure daily exercise for every child, with about 71% of Finnish early childhood education units participating. The “Families on the Move” programme, since 2020, uses a multisectoral approach to support professionals promoting active lifestyles for families. Educational institutions’ operational culture significantly impacts physical activity, as does active family time, which strongly influences lifelong physical activity habits. Active commuting, environmental exploration, and time in nature/built environments are important for early childhood development.Project Description: The Adventure Campaign encourages families to be physically active during everyday trips, on the way from home to early childhood education, by going out to explore the immediate surroundings of the home or even on a trip to the store. Free materials are available online (available in English), yearly updated campaign posters and adventure bingo cards for activities and task cards for organising yard events. Campaign provides tools for early childhood education units to collaborate with families in accordance with the early childhood education plan and recommendations for physical activity in the early years. The campaign is also promoted on social media.Conclusion: In 2024, the campaign reached 43% of Finnish early childhood education units, 107 other organisations from 225 municipalities, and 100,000 families. Feedback has been collected from families who participated in the Adventure Campaign over the years. Based on the responses, the campaign has brought joy to families and encouraged them to exercise more together. Families enjoy outdoor activities together in the local nature. Feedback from early childhood educators shows that the Adventure Campaign and its materials have been received with joy and actively used in kindergartens and family daycare centres, even though the primary target group of the campaign is families. Early childhood educators felt that the campaign especially increased everyday physical activity and children’s participation in early childhood education.